Receptor tyrosine kinase expression and phosphorylation in canine nasal carcinoma. (December 2017) - Hocker, Samuel E.; Higginbotham, Mary Lynn; Schermerhorn, Thomas; Henningson, Jamie
Abstract: Preliminary studies have supported use of toceranib phosphate (Palladia®) in treatment of canine nasal carcinomas, though the mechanisms of its activity are unknown. This study evaluated sixteen canine nasal carcinoma and five normal nasal epithelium samples for expression and phosphorylation of known targets of toceranib [vascular endothelial growth factor receptor-2 (VEGR2), platelet derived growth factor alpha (PDGFR-α), platelet derived growth factor receptor beta (PDGFR-β), and stem cell factor receptor (c-KIT)] and epidermal growth factor receptor 1 (EGFR1) using immunohistochemistry, RT-PCR and a receptor tyrosine kinase (RTK) phosphorylation panel. Protein for VEGFR2 was expressed in all carcinomas, PDGFR-α was noted in 15/16, whereas PDGFR-β was detected in 3/16 samples, but showed significant stromal staining. Protein expression for c-KIT was present in 4/16 and EGFR1 was noted in 14/16 samples. Normal tissue showed variable protein expression of the RTKs. Messenger RNA for VEGFR2, PDGFR-β, and c-KIT were noted in all samples. Messenger RNA for PDGFR-α and EGFR1 were detected in 15/16 samples. All normal nasal tissue detected messenger RNA. Phosphorylation of VEGFR2, PDGFR-α, PDGFR-β and c-KIT was not observed in any carcinoma or normal nasal sample, but phosphorylation of EGFR1 was noted in 10/16 carcinoma and 3/5 normal samples. The absence of phosphorylated RTK targets of toceranib suggests any clinical effect of toceranib occurs through inhibition of alternative unidentified RTK pathways in canine nasal carcinomas. The observed protein and message expression and phosphorylation of EGFR1 in the nasal carcinoma samples merits further inquiry into EGFR1 as a therapeutic target for this cancer. Highlights: Several targets of toceranib phosphate were expressed at the protein level. Epidermal growth factor receptor may represent a potential treatment target. Targets of toceranib phosphate were not phosphorylated.